Development of Marine-Based High-Protein Powder from Crabs and Its Nutritional Characterization - Souvik Bisui; Rita Mondal; Ranajit Kumar Khalua (The Bioscan, 2026)
The increasing demand for high-protein functional foods has led to the exploration of marine resources as sustainable protein sources. Crab meat, known for its high-quality protein and essential nutrients, offers significant potential for value-added product development. This study focuses on the development of high-protein powder from different crab species and evaluates its physicochemical, nutritional, and functional properties. Crab meat from selected species was processed through cleaning, cooking, drying, and grinding to obtain protein-rich powder. The developed powders were analyzed for moisture, protein, fat, ash, and mineral content. Results indicated that crab-based powders contain approximately 17–20% protein per 100 g, with low fat and carbohydrate levels, making them suitable as functional food ingredients. The study highlights the feasibility of utilizing crab processing waste and underutilized species for nutritionally enriched powder production.